2022
DOI: 10.3390/ijerph19159301
|View full text |Cite
|
Sign up to set email alerts
|

Bullying in Adolescents: Differences between Gender and School Year and Relationship with Academic Performance

Abstract: School bullying is a phenomenon of unjustified aggression in the school environment that is widespread throughout the world and with serious consequences for both the bully and the bullied. The objectives of this research were to analyze the differences between the different bullying categories by gender and academic year in primary and secondary education students, as well as their relationship with academic performance. To categorize students according to their bullying experiences, the European Bullying Int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 54 publications
2
9
1
Order By: Relevance
“…Initially, the descriptive gender-based differences found in this study suggest a considerably gendered state of affairs regarding teenagers’ self-reported perception of bullying victimization and symptomatology (passive factors) and intimidation (active bullying behaviors). The outcomes of these comparisons, carried out using robust mean tests, show great agreement with the findings of both qualitative [ 25 ] and quantitative [ 34 , 52 ] previous studies, regarding the greater involvement in active bullying behaviors among male students, compared with their female counterparts. Coherently, a recent study [ 63 ] has found a greater affectation among females as a consequence of their exposure to relational peer-to-peer bullying behaviors in a passive role.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…Initially, the descriptive gender-based differences found in this study suggest a considerably gendered state of affairs regarding teenagers’ self-reported perception of bullying victimization and symptomatology (passive factors) and intimidation (active bullying behaviors). The outcomes of these comparisons, carried out using robust mean tests, show great agreement with the findings of both qualitative [ 25 ] and quantitative [ 34 , 52 ] previous studies, regarding the greater involvement in active bullying behaviors among male students, compared with their female counterparts. Coherently, a recent study [ 63 ] has found a greater affectation among females as a consequence of their exposure to relational peer-to-peer bullying behaviors in a passive role.…”
Section: Discussionsupporting
confidence: 85%
“…Regarding other age-based prevalence rates, a recent study [ 33 ] reported a prevalence (victimization and perpetration) among youth students that was approximately 50% lower than that observed among pre-adolescent students in Brazil. In Spain, the role of bully has shown a higher prevalence between 11 and 15 years of age (between 1st and 4th secondary grades) [ 34 ], coherently with the data reported by studies addressing other Hispanic samples [ 35 , 36 ].…”
Section: Introductionsupporting
confidence: 73%
See 2 more Smart Citations
“…A study conducted on American high school students showed that a low self-perception of academic performance was associated with being involved in a physical fight [ 44 ]. A Spanish study reported that students in the role of the bully/victim had lower academic performance, compared with those in non-bully/non-victim [ 45 ]. Bullying has a dual direction, such that being bullied may lead to future aggressive behaviors [ 46 ].…”
Section: Discussionmentioning
confidence: 99%